Formation of an Information (digital) Society in Ukraine Under Martial Law: Political and Legal Aspect - Kyrychenko , Yurii; Postol , Olena; Riezanova , Natalia; Nazarenko , Pavlo; Baieva , Liliia (Jurnal Cita Hukum, 2026)
In addition to analyzing the political and legal frameworks for guaranteeing the digital transformation of the state in the face of military aggression, the paper looks at the characteristics of the development of an information (digital) society in Ukraine under martial law. The topic is relevant because information and communication technologies are rapidly permeating every aspect of public life in the modern stage of society's development, creating a new model of socioeconomic and political development known as the information or digital society. In order to maintain the stability of state administration, the continuation of administrative services, and efficient communication between the state and its citizens, the Russian Federation's full-scale war against Ukraine created new difficulties for the operation of state institutions. This made the active use of digital technologies necessary. The dominance of knowledge and information as strategic resources for development, the extensive use of digital technologies, the expansion of information access, and the active use of electronic services in the field of public administration are found to be characteristics of the information society. In this sense, digitalization is viewed as a complicated process that uses contemporary information technologies to change public communications, economic interactions, and state institutions. The study also takes into account cyber and information security as a crucial element in the development of a digital society.